Предмет: Алгебра,
автор: oldside
Вычислить интеграл
Приложения:
Ответы
Автор ответа:
1
1) ∫²₋₂ (1 - 3x²)dx = (x - x³)|²₋₂ = (2 - 2³) - (-2 - (-2)³) = (2 - 8) - (-2 + 8) = 2-8+2-8 = 4 - 16 = -12
2) ∫⁻¹₋₂ (6x² + 2x -10)dx = (2x³ + x² - 10x)|⁻¹₋₂ = (2*(-1)³ + (-1)² - 10*(-1)) - (2*(-2)³ + (-2)² - 10*(-2)) = -2 + 1 + 10 - (-16 + 4 + 20) = -2 + 11 + 16 - 24 = 1
Похожие вопросы
Предмет: Литература,
автор: nargizaamonova92
Предмет: Алгебра,
автор: shiloden111
Предмет: Қазақ тiлi,
автор: kucherbaevshami
Предмет: Математика,
автор: Аноним
Предмет: История,
автор: умница445